Implementation of Problem Based Learning to Improve Learning Outcomes of Backhand Stroke Skills in Badminton Games - Muhammad Yusran; Wilhelmina Unmehopa; Siti Divinubun; Johanna Matitaputty (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2026)
This study aims to improve the learning outcomes of backhand stroke skills in badminton through the application of the Problem Based Learning (PBL) model in grade VIII students of SMP Negeri 6 Ambon. The study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model which was implemented in two cycles, each including the planning stage, action implementation, observation, and reflection. The research subjects were 28 students. Data collection was carried out through skills tests, observation, and documentation, while data analysis used quantitative descriptive analysis based on the percentage of learning completion. The results showed that the application of PBL was able to improve the learning outcomes of backhand stroke skills. In cycle I, 19 students (68%) achieved learning completion, while 9 students (32%) had not yet completed it. After improvements were made to learning in cycle II, all students (100%) achieved learning completion. In addition to improving learning outcomes, the application of PBL also encouraged increased active participation, critical thinking skills, cooperation, and student confidence during the learning process. These findings indicate that the Problem Based Learning model is effective in improving learning outcomes of backhand stroke skills in physical education learning at the junior high school level